2022
DOI: 10.1002/mnfr.202200204
|View full text |Cite
|
Sign up to set email alerts
|

Reverting to a Healthy Diet during Lactation Normalizes Maternal Milk Lipid Content of Diet‐Induced Obese Rats and Prevents Early Alterations in the Plasma Lipidome of the Offspring

Abstract: This study aims to assess in rats whether normalizing maternal diet during lactation prevents the harmful effects of western diet (WD) consumption during the whole perinatal period on the lipidomic profile in maternal milk and offspring plasma. Methods and Results: Control dams (CON-dams), fed with standard diet (SD); WD-dams, fed with WD prior and during gestation and lactation; and reversion dams (REV-dams), fed as WD-dams but moved to SD during lactation are followed. Lipidomic analysis is performed in milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…This was tentatively related to the intake of higher amounts of leptin from maternal milk during the suckling period (due to greater maternal adiposity) in the absence of alterations in maternal diet. Taken together, these results would be in accordance with a greater influence of maternal diet on milk composition and on offspring metabolic programming, rather than maternal obesity per se, as previously proposed [ 9 , 10 ].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This was tentatively related to the intake of higher amounts of leptin from maternal milk during the suckling period (due to greater maternal adiposity) in the absence of alterations in maternal diet. Taken together, these results would be in accordance with a greater influence of maternal diet on milk composition and on offspring metabolic programming, rather than maternal obesity per se, as previously proposed [ 9 , 10 ].…”
Section: Discussionsupporting
confidence: 91%
“…In this regard, we have previously shown that implementation of a healthy diet during lactation in diet-induced obese dams attenuates detrimental programming effects in their offspring observed at an early age [ 9 ]. This was associated with the normalization of milk composition [ 9 , 10 ]. Here, in the same cohort studied at early age [ 9 ], it is also highlighted that maternal intake of an obesogenic diet before and during gestation and lactation has detrimental effects on the phenotype of the adult offspring, and that these effects are magnified by exposure to WD conditions after weaning.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations